Design of high-rate long-length structured QC-LDPC with good error performance - Xiong Yin; Zhaoxia Zheng; Yi Dan; Zhenglin Liu (2011 5th International Conference on Signal Processing and Communication Systems, 2011)
In order to improve error performance of data storage, this paper presents a code-design algorithm for a class of structured quasi-cyclic low-density parity-check (SQC-LDPC) codes with high rate ( R >;= 0.9 ) and long-length (10 4 <; 60 n). In the design of parity-check matrix, optimized degree distribution pairs are obtained based on the combination of density evolution and differential evolution with a modified cost function. Moreover, both fewer short block-cycles and larger approximated cycle extrinsic message degree (ACE) are also considered. Simulation results indicate that codes in this design method its simulation curve is close to Shannon limit and have lower error floor.